From The Flame and the Flower to Fifty Shades of Grey: Sex, Power and Desire in the Romance Novel - Nilson, Maria (Academic Quarter | Akademisk kvarter, 2013)
E.L. James’s Fifty Shades trilogy has become a huge success and soldmillions of copies. The novels’ mix of romance and erotica has beendescribed as something new. Reading these books mainly as romance, Nilson focuses on how James uses well known and established romance traits from, for example, the so-called “bodice-ripper” novel and chick lit, in order to create a hybrid. These traits arevisible in both how James describes her protagonists and in howthe relationship between them is portrayed. Nilson argues that theFifty Shades trilogy is, rather than a new kind of romance, a compilation of well-established traits.